LIQUIDITY ANALYTICS FOR MICRO, SMALL, AND MEDIUM ENTERPRISES - Dicky Perwira Ompusunggu; Sri Wiyanti2, Dahlia; Dahlia; Nadia Anggreani; Luthfia Ananda (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Businesses, including UMKM, are heavily dependent on liquidity. The aim of this study is to see how liquidity affects the viability and growth of small and medium-sized enterprises. (UMKM). Liquidity is measured using a smooth and fast ratio, which shows UMKM's ability to meet its short-term obligations. Data collected from interviews and surveys with UMKM owners in various industries. The results of the analysis show that liquidity greatly affects the viability of micro, small, and medium-sized enterprises. (UMKM). UMKMs with high levels of liquidity are more able to meet short-term obligations, take advantage of investment opportunities, and adapt better to economic shocks. However, small and medium-sized enterprises (SMEs) with low liquidity tend to face financial problems and risk bankruptcy. The study provides practical advice for UMKM in managing liquidity, such as effective cash saving, business debt management, and stock optimization. In addition, the study highlights the importance of increasing UMKM's liquidity by accessing external funding sources such as bank loans or investments.